The occurrence of repeated high acceleration ability (RHAA) in elite youth football - Serpiello, F. R.; Duthie, G. M.; Moran, C.; Kovacevic, D.; Selimi, E.; Varley, M. C. (International Journal of Sports Medicine, 2018)
The aim of the present study was to investigate the occurrence of Repeated High-Acceleration Ability (RHAA) bouts in elite youth football games using 10-Hz GPS devices and two relative thresholds derived from players` actual maximal acceleration. Thirty-six outfield soccer players (age 14.9±0.6 years) participated in the study. Players wore 10-Hz GPS units during 41 official games. High accelerations were defined as efforts commencing above a threshold corresponding to 70% (T70%) or 80% (T80%) of the average 5-m acceleration obtained during a 40-m sprint test; RHAA bouts were defined as =3 efforts with =45 s recovery between efforts. Results were analysed via generalised linear mixed model and magnitude-based inferential statistics. On average, 8.0±4.6 and 5.1±3.5 bouts were detected in an entire game using T70% and T80%, respectively. When all positions were analysed together, there was a very-likely small difference in the number of RHAA bouts between first and second half for T70% and T80%, respectively. RHAA bouts occur frequently in elite youth football, with small differences between halves and between playing positions within the first or second half in most variables assessed.